Seroprevalence of Campylobacter-Specific Antibodies in two German Duck Farms – A Prospective Follow-Up Study - Masanta, Wycliffe Omurwa (Eur J Microbiol Immunol (Bp), 2016)
Several studies have shown that about 60–100% of farmed ducks are colonized by Campylobacter species. Because of this, a higher risk of campylobacteriosis among duck farm workers can be assumed. To estimate the risk of Campylobacter infections in duck farm workers, we investigated the prevalence of Campylobacter spp. in ducks of two duck farms and the seroprevalence of anti-Campylobacter antibodies (IgA and IgG) in two cohorts of workers. The first cohort consisted of high-exposed stable workers and slaughterers, which was compared to a second cohort of non-/low-exposed persons. Duck caecal swabs and serum samples were collected in 2004, 2007, and 2010. The colonization rate in the examined ducks was found to be 80–90%. The seroprevalence of anti-Campylobacter IgA and IgG antibodies among the non-exposed cohort was found to be 0.00% in all 3 years. In contrast, the exposed cohort demonstrated an IgA seroprevalence of 4.17% in 2004, 5.71% in 2007, and 0.00% in 2010 and an IgG seroprevalence of 8.33% in 2004, 0.00% in 2007, and 4.29% in 2010. In conclusion, in 2004, we observed a significantly higher anti-Campylobacter antibody seroprevalence in the exposed cohort followed by a steady reduction in 2007 and 2010 under occupational health and safety measures.